Diplomatic Language: An Analysis of Salutations from Speeches used in International Diplomacy - Pokharel, Surendra (Journal of International Affairs, 2020)
This paper analyzes the core aspects of diplomatic salutations through the discussion of speeches used at international summits. Speeches by heads of states were chosen from two Non-Aligned Movement (NAM) Summits (1989, 2005), South Summit of Group 77 and China (2005), Islamic-American Summit (2017) and Brazil, Russia, India, China, South Africa (BRICS) Summit (2018). Examining the context of salutations from the summits mentioned above, this paper aims to provide some insight into the international diplomatic protocol of salutations as applied at international gatherings. Research findings suggest that most leaders use salutations in a way that reflects their position within the political and cultural systems of their respective countries.